2014
DOI: 10.1108/gs-10-2013-0023
|View full text |Cite
|
Sign up to set email alerts
|

Covered solution for a grey linear program based on a general formula for the inverse of a grey matrix

Abstract: Purpose – This paper attempts to establish the general formula for computing the inverse of grey matrix, and the results are applied to solve grey linear programming. The inverse of a grey matrix and grey linear programming plays an important role in establishing a grey computational system. Design/methodology/approach – Starting from the fact that missing information often appears in complex systems, and therefore that true values of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…In some cases, after solving the grey model, some points of the obtained solution are out of the feasible region. In another study, Li, Liu, and Wang (2014) improved covered solution, but this method suffers from some specific shortcomings including a high volume of calculations and a need to reduce the length of grey parameters. Mahmoudi, Liu, Javed, and Abbasi (2019) proposed a novel method to overcome the aforementioned shortcomings.…”
Section: Grey System Theorymentioning
confidence: 99%
“…In some cases, after solving the grey model, some points of the obtained solution are out of the feasible region. In another study, Li, Liu, and Wang (2014) improved covered solution, but this method suffers from some specific shortcomings including a high volume of calculations and a need to reduce the length of grey parameters. Mahmoudi, Liu, Javed, and Abbasi (2019) proposed a novel method to overcome the aforementioned shortcomings.…”
Section: Grey System Theorymentioning
confidence: 99%
“…Hajiagha et al (2012) proposed a method to solve the GLP problem by using a multi-objective concept, yet their method presented the wrong solution for GLP problems as proved by Mahmoudi et al (2018a). Li et al (2014) proposed a method based on the concept of Covered Solution method, yet it had some problems, similarly as Li (2007)'s method. Nasseri et al (2016) presented a new method using the primal simplex algorithm to solve GLP problems, but their method could solve the GLP problems just with the grey objective function.…”
Section: Grey Linear Programming (Glp)mentioning
confidence: 99%
“…There is always some uncertainty about time duration of the activities in the network planning, due to which the fuzzy critical path method (FCPM) was proposed since the late 1970s (Kumar & Kaur, 2010).…”
Section: Ekonomika a Managementmentioning
confidence: 99%
“…Many researches focused on development of a new fuzzy critical path method based on the fuzzy set theory to solve the project scheduling problem under the fuzzy environment (Kumar & Kaur, 2010;Chen & Hsueh, 2008;Shankar & Saradhi, 2011;Liang & Han, 2004). As an application, Han, Chung, and Liang (Han et al, 2006) demonstrated a model for how to employ the Fuzzy Critical Path method (CPM) to fi nd out airport's ground critical operation processes.…”
Section: Ekonomika a Managementmentioning
confidence: 99%
See 1 more Smart Citation